PENERAPAN GAME ANALISIS ASAH OTAK UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR SISWA DALAM MENULIS BIOGRAFI - Wijaya, Aang Saepuloh Akbar; Herlianti, Rizqi Awalya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Students' understanding of writing biographical texts identified is still less active and learning outcomes are not good, so it is feared that it will decrease further. The alternative used by researchers is the application of game learning strategies to brain teaser analysis that aims to improve student activity and learning outcomes in biographical writing skills. The researcher used the pre-experimental design research design through the one-group-pretest-posttest approach. Data collection used is the plan for implementing learning, observation, and testing. Samples taken by researchers in the X3 class of SMAN 5 Subang were 30 students. The results of the initial value analysis and final value analysis of students show an increase in writing skills in biographical text material. The results of the observation of teacher learning in the 90% class were carried out and student learning in the 85% class was conducted. In the pre-test, student activeness was only 63%, with details of 19 students active students, and student work results, 5 students got high scores, 14 moderate grades, and 11 low scores, then after being given treatment with game learning strategies obtained brain teaser analysis the results of the post-test activities of students increased to 90%, with details of active students 27 students, and the work results of students who scored high 12 students, moderate grades 15 students, and low scores 3 students. Thus the application of game learning strategies to brain teaser analysis has a positive impact, namely a significant increase in learning outcomes, both activeness and the value of learning outcomes obtained.